Effectiveness of removable expander appliances in posterior crossbite: A review of the literature (Research, Society and Development, 2024)
Objective: To evaluate the effectiveness of removable expander appliances in the treatment of posterior crossbite by reviewing and analyzing clinical studies, scientific articles and published case reports. Background: Posterior crossbite is a dental malocclusion characterized by a transverse misalignment of the upper and lower teeth, where the upper teeth bite into the lower teeth. This condition can affect one or more dental organs and if left untreated, can lead to functional and esthetic problems, as well as imbalances in maxillofacial growth. Early correction of posterior crossbite is crucial to avoid future complications such as uneven tooth wear, temporomandibular dysfunction and facial asymmetries, and different treatment methods have been used, including removable appliances. Methodology: The research was structured from a search tree (PubMed, Scielo, Google Scholar, Dialnet, Scopus), with keywords such as: removable expandable appliance; posterior crossbite; removable orthodontics; treatment efficacy AND posterior crossbite; posterior crossbite NOT fixed appliance. Conclusions: Removable expander appliances are an effective option for treating posterior crossbite in children. Studies show that these devices correct malocclusion, promote maxillary growth and improve dental alignment. The effectiveness of the treatment depends on the cooperation of the child and parents. The choice of appliance should be based on a careful evaluation of the patient's needs, considering cooperation, severity of the malocclusion and the preferences of the patient and the orthodontist.